Biomechanical study of a biplanar double support screw (BDSF) technique based on Pauwels angle in femoral neck fractures: finite element analysis - Tang, Zhongjian; Zhang, Yazhong; Huang, Shaolong; Zhu, Zhexi; Zhou, Chengqiang; Zhu, Ziqiang; Wang, Yunqing; Wang, Bin (Frontiers in Bioengineering and Biotechnology, 2024)
The objective of the present study is to conduct a comparative analysis of the biomechanical advantages and disadvantages associated with a biplanar double support screw (BDSF) internal fixation device.Methods: Two distinct femoral neck fracture models, one with a 30°angle and the other with a 70°angle, were created using a verified and effective finite element model. Accordingly, a total of eight groups of finite element models were utilized, each implanted with different configurations of fixation devices, including distal screw 150°BDSF, distal screw 165°BDSF, 3 CLS arranged in an inverted triangle configuration, and 4 CLS arranged in a "α" configuration. Subsequently, the displacement and distribution of Von Mises stress (VMS) in the femur and internal fixation device were assessed in each fracture group under an axial load of 2100 N.Results: At Pauwels 30°Angle, the femur with a 150°-BDSF orientation exhibited a maximum displacement of 3.17 mm, while the femur with a 165°-BDSF orientation displayed a maximum displacement of 3.13 mm. When compared with the femoral neck fracture model characterized by a Pauwels Angle of 70°, the shear force observed in the 70°model was significantly higher than that in the 30°model.Conversely, the stability of the 30°model was significantly superior to that of the 70°model. Furthermore, in the 70°model, the BDSF group exhibited a maximum femur displacement that was lower than both the 3CCS (3.46 mm) and 4CCS (3.43 mm) thresholds.The biomechanical properties of the BDSF internal fixation device are superior to the other two hollow screw internal fixation devices. Correspondingly, superior biomechanical outcomes can be achieved through the implementation of distal screw insertion at an angle of 165°. Thus, the BDSF internal fixation technique can be considered as a viable closed reduction internal fixation technique for managing femoral neck fractures at varying Pauwels angles.